2015
DOI: 10.1111/jch.12608
|View full text |Cite
|
Sign up to set email alerts
|

Is Daytime Systolic Load an Important Risk Factor for Target Organ Damage in Pediatric Hypertension?

Abstract: The aim of this study was to compare ambulatory blood pressure (BP) monitoring (ABPM) data and determine which hypertension type is a risk factor in target organ damage. A total of 82 children (47 boys) with suspected hypertension based on office BP measurements and considered hypertensive by ABPM were studied. Target organ damage included the following: 35.3% hypertensive retinopathy, 25.6% microalbuminuria, 15.8% increased left ventricular mass index, 29.2% increased carotid intima-media thickness (cIMT), 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
0
35
0
3
Order By: Relevance
“…In the study of Conkar, et al frequency of hypertensive retinopathy is found as 35.3% whereas Williams, et al mentioned it as 18% [20,21]. We found hypertensive retinopathy in 47 patients (20.3%).…”
Section: Discussionmentioning
confidence: 45%
“…In the study of Conkar, et al frequency of hypertensive retinopathy is found as 35.3% whereas Williams, et al mentioned it as 18% [20,21]. We found hypertensive retinopathy in 47 patients (20.3%).…”
Section: Discussionmentioning
confidence: 45%
“…In adults, microalbuminuria has been shown to be a marker of HTN-induced renal injury (33). However, pediatric ABPM studies have not demonstrated ABPM parameters to independently predict presence of microalbuminuria in non-diabetic children and adolescents to date (34, 35). …”
Section: Pediatric Abpm Outcome Datamentioning
confidence: 99%
“…Поэтому с целью минимизировать влияние пола, возраста и ожирения у лиц моложе 18 лет для определения гипертрофии миокарда левого желудочка используют индекс массы миокарда ле-вого желудочка, индексированный по росту, возве-денному в степень 2,7. Гипертрофия миокарда левого желудочка диагностируется в случае, если средний уровень индекса массы миокарда левого желудочка равен или превышает 95-й перцентиль кривой рас-пределения этого индекса в популяции для соответ-ствующего возраста и пола [8].…”
Section: характеристика детей и методы исследованиunclassified